PENGARUH KUALITAS PELAYANAN, BRAND IMAGE LEMBAGA DAN KEPERCAYAAN TERHADAP KEPUTUSAN MEMILIH UNIVERSITAS Prof. Dr. HAZAIRIN, S.H SEBAGAI TEMPAT KULIAH - Virgiawan, Dio (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
This research aims to determine The Influence Of Service Quality, Institutional Brand Image And Trust On The Decision To Choose Prof. Dr. Hazairin, S.H University As A Place To Study. This type of research uses quantitative descriptive research methods. The population used in this research were students from Prof. Dr. Hazairin, S.H University. The number of respondents in this study was 85 people. The data collection method uses a questionnaire and uses analysis techniques using multiple linear regression analysis tests and hypothesis testing, namely the t test and f test. Based on the results of multiple linear regression, the form of the regression equation Y = 5.574 + 0.488 (X_1) + 0.357 (X2) + 0.204 (X3) is obtained and the results of the t test and f test of this research can be concluded that Service Quality has a significant effect on Decisions, this is proven by the results The t test shows the value of tcount > ttable (3.800 > 1.66388) and (sig α = 0.000 < 0.050). This means H_0 is rejected and H_a is accepted. The Institution's Brand Image has a significant influence on decisions, this is proven by the results of the t test showing the value of tcount > ttable (5.421 > 1.66388) and (sig α = 0.000 < 0.050). Trust has a significant effect on decisions, this is proven by the results of the t test showing the value of tcount > ttable (2.252 > 1.987) and (sig α = 0.002 < 0.050). This means that H_0 is rejected and H_a is accepted. This means H_0 is rejected and H_a is accepted. Service Quality (X1), Institutional Brand Image (X2) and Trust (X3) together have a significant influence on Decisions (Y), this is proven by the F test showing the value of fcount > ftable, namely (27.877 > 2.72) and (sig α = 0.000 < 0.050). This means H_0 is rejected and H_a is accepted. Keywords: Service Quality, Institutional Brand Image, Trust; Decision